National summary reports on pesticide residue analysis performed in 2018. Issue 4 (2nd April 2020) - ,
Abstract : In accordance with Article 31 of Regulation (EC) No. 396/2005, European Union (EU) Member States have to communicate to the European Food Safety Authority (EFSA) the results of their official controls on pesticide residues in food. In the framework of this communication, the EU Member States, Iceland and Norway provided a short summary report outlining the main findings of the control activities during the reference year. This technical report is the compilation of the contributions of the reporting countries. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2020.6057/full